SOX9: a novel janus-faced regulator in immunity and its promise as a therapeutic target - Shi, Qian; He, Shouyu (Frontiers in Molecular Biosciences, 2025)
BackgroundThe Sex-determining Region Y-related High-Mobility Group Box 9 (SOX9), a key transcription factor in the SOX family, plays essential roles in various biological processes, particularly in the development of the tumor microenvironment and the repair of inflamed tissues.FindingsThis review elucidates the structure of SOX9 and its relationship with immune components from an immunological perspective, it analyzes the mechanisms by which SOX9 operates in tumor immune escape, inflammatory diseases and tissue repair (such as in osteoarthritis, OA), Furthermore, it introduces a novel immunological perspective by investigating the therapeutic potential and application strategies of SOX9 for treating tumors and inflammatory diseases. and reviews the latest advances in SOX9-related treatments.ConclusionSOX9 plays a complex and dual role in immunology, acting as a “double-edged sword”. On one hand, it promotes immune escape by impairing immune cell function, making it a potential therapeutic target in cancer. On the other hand, increased levels of SOX9 help maintain macrophage function, contributing to cartilage formation, tissue regeneration, and repair. Given its significant role in immunobiology, SOX9 represents a promising therapeutic candidate for cancer and immune-related diseases.